An Evaluation of the Potential Radiosensitization Effect of Spherical Gold Nanoparticles to Induce Cellular Damage Using Different Radiation Qualities - Monique Engelbrecht-Roberts; Xanthene Miles; Charlot Vandevoorde; Maryna de Kock (Molecules)
Global disparities in cancer prevention, detection, and treatment demand a unified international effort to reduce the disease’s burden and improve outcomes. Despite advances in chemotherapy and radiotherapy, many tumors remain resistant to these treatments. Gold nanoparticles (AuNPs) have shown promise as radiosensitizers, enhancing the effectiveness of low-energy X-rays by emitting Auger electrons that cause localized cellular damage. In this study, spherical AuNPs of 5 nm and 10 nm were characterized and tested on various cell lines, including malignant breast cells (MCF-7), non-malignant cells (CHO-K1 and MCF-10A), and human lymphocytes. Cells were treated with AuNPs and irradiated with attenuated 6 megavoltage (MV) X-rays or p(66)/Be neutron radiation to assess DNA double-strand break (DSB) damage, cell viability, and cell cycle progression. The combination of AuNPs and neutron radiation induced higher levels of γ-H2AX foci and micronucleus formation compared to treatments with AuNPs or X-ray radiation alone. AuNPs alone reduced cellular kinetics and increased the accumulation of cells in the G2/M phase, suggesting a block of cell cycle progression. For cell proliferation, significant effects were only observed at the concentration of 50 μg/mL of AuNPs, while lower concentrations had no inhibitory effect. Further research is needed to quantify internalized AuNPs and correlate their concentration with the observed cellular effects to unravel the biological mechanisms of their radioenhancement.